Bridging Human Rights and Nature Protection: Exploring the Potential of the Anthropocentric Approach - Wiater-Hellgardt, Patricia (Human rights quarterly, 2025)
The article explores the doctrinal potential of anthropocentric human rights law to support nature protection, proposing a conception of human rights that is aligned with ecological well-being. Using the case law of the ECtHR as an example, it argues that the full potential of this framework has yet to be realized. The article further explores how the ECtHR’s evolving stance on victim status and remedies, coupled with its approach to the standing of associations in climate change cases, could open new avenues for ad dressing nature protection. While recognizing the symbolic power of Rights of Nature, it concludes that, in light of the ecological shift in human rights law, the practical basis for adopting Rights of Nature remains limited.
CRIS-Team Scopus Importer:2025-09-12